Continuance intention to use e-wallet as a payment instrument among generation z in Malaysia– a behavioural study - Wong, Xin Yan (2023)
E-Wallet is adopted for online transactions through a computer or a phone. E-Wallet usage has grown during the pandemic but fell after the pandemic. This report will discuss the problem that users confronting when continue using E-Wallet. Since a sizable group exists in Malaysia, this research will focus on Generation Z (71%). Then, this research will provide managerial decision-makers with a beneficial indication of how to improve and persuade users to continue using E-Wallet based on a few primary factors. It has also given academics more understanding of why this topic should be studied and how this study is unique from others. This project has adopted the Mobile Technology Acceptance Model, which included four variables: mobile usefulness, ease of use, security risk, and trust toward the service provider to define the continuance intention. Since limited research examines the MTAM model for E-Wallet, the current author will propose a new conceptual framework and validate the relationship between IVs and DV. This research applies the quantitative approach, which is used to measure numerical data. The current author created the questionnaire that measured the variables by adopting 5 points Likert Scale (Strongly disagree, disagree, neutral, agree, strongly agree). Next, the current author distributed it to the 384 respondents using purposive sampling. Then, the current researcher will collect the questionnaire response and use those data to perform a test analysis like descriptive, inferential, and correlation results. Based on the findings, the mobile perceived security risk is an insignificant variable. Further, the interpretations of the hypothesis findings will also be discussed whether the research objectives are achieved. It will also present the recommendation that solves the inefficiency of each hypothesis that provides indications for managerial decision-makers and academics. Lastly, the project limitations have been discussed, and this project has proposed recommendations and offered guidance to future researchers.